A Preliminary Report on the Karao Language in Benguet - Moriguchi, Tsunekazu (The Archive; Vol 4 (1984): Publication Four: Studies on Philippine Minor Languages, 2025)
The Karao language is a minority language in Bukod, Benguet and is spoken only in two barrios—Karao and Ikip—which belonged to one barrio before.   The people in Karao and Ikip are tri-linguals: Karao, Inibaloy and Ilocano. Inibaloy is a lingua franca in Bukod and its vicinity, and Ilocano for Benguet province. Although the people speaking Karao have been assimilated into the Inibaloy culture and language with a lot of words observed in the language, Karao still keeps its independency. Even the people in Bukod, which lies only 6 kilometers from Karao, can not understand the Karao language and its cognate languages have not been identified yet.